Procurement 4.0 and organizational performance in the Malaysian construction industry - Lee, Khai Loon; Shaharud-din, Afiq Muqri (IGI Global, 2022)
Procurement 4.0 is the result of the industrial revolution (IR) 4.0 technologies implemented into the organization. The incorporation of IR 4.0 with the procurementsystem in the Malaysian construction industry is still low because of the lack of expertise available to adopt the technology. Therefore, this study investigated relationships between procurement 4.0 elements, organizational performance, and mediating effect of intention to optimize the procurement process. To support this study, resourcebased view theory and theory of planned behaviour were applied. This study focuses on 5267 G7 Malaysia construction companies. 413 online survey questionnaires were distributed using cluster random sampling techniques, and 134 responses were successfully acquired, representing 32.45% of the response rate. SmartPLS was used to analyze the data. Seven hypotheses are supported, while three are not supported. The mediating effect of intention to optimize the procurement process is significant only in the relationship between procurement 4.0 strategy and organizational performance.